The impact of increased temperatures on germination patterns of semi-aquatic plants. Issue 3 (2nd September 2019) - Dessent, Jade; Lawler, Susan; Nielsen, Daryl
Abstract: Future climate change predictions indicate that there will be an increase in ambient air temperature. Increases in ambient air temperature will result in a corresponding increase in soil temperature. The consequences of further increases in soil temperature will potentially be detrimental for the soil seed bank of plants in terms of length of dormancy and viability of seeds. This experiment investigated the effect of different exposure temperatures and duration of exposure on the germination of semi-aquatic plant species. Seeds of four species ( Alternanthera denticulata, Juncus usitatus, Persicaria lapathifolia and Persicaria prostrata ) were exposed to temperatures ranging from 25 to 100°C for durations between 1 and 14 days, before being germinated in an incubator for 6 weeks. Germination occurred in all four species after exposure to temperatures ranging from 25 to 60°C. These temperatures appeared to promote germination as the temperature and duration of exposure increased. However, in P. lapathifolia and P. prostrata, the number of seeds germinating declined when exposed to 70°C and there was no germination for temperatures exceeding this. In contrast, A. denticulata and J. usitatus only began to decline when exposed to 80°C, with no germination at higher temperatures. These results suggest that soil temperatures exceeding potential threshold temperatures of 70 and 80°C will result in a decline in the number of seeds germinating and may potentially see a change in species distributions. As such soil temperatures are already being experienced throughout Australia, some species may already be close to their thermal threshold.